Mauriac: The Ambivalent Author of Absence - James H. Reid (Studies in 20th & 21st Century Literature, 1987)
This essay explores the significance of first- and third-person narrative voices. Although, as Gérard Genette points out, the choice of either voice is not in itself significant, transitions between the two voices are. Such transitions serve to disclose the absence of an author's point of view. They are a privileged means of revealing that no narrative voice can be entirely truthful or persuasive. In two Mauriac novels, Thérèse Desquevroux and Le Noeud de vipères, transitions between first- and third-person voices are produced by linguistic differences between the "I" and the "he." These differences create a rhetoric of voice: the "he" hides and figures an implicit "I," while the "I" hides and figures an implicit "he." This rhetoric generates opposing plots recounting both the author's and the reader's search for a hidden, truthful voice: for an implied writer or reader. One plot traces an effort to disclose, within an inauthentic "he," a hidden, authentic "I." It culminates only in a recognition of the formal nature of all stories and all voices that tell them. The other plot recounts the discovery that the "I" hides a "he." It reveals a very different truth: that the "I" is alienated from its formal role and from the formal nature of the narratives it recounts. Both of these plots are linear accounts of how the narrative was composed and how it should be interpreted. Both create seemingly truthful voices—implied writers or readers—who tell them. But because these plots represent the same narrative in contradictory terms, they ultimately demonstrate the impossibility of saying what the narrative is doing or who, if anyone, is doing the narrating. Indeed, Mauriac's characters ask whether the writing and reading of narrative do anything at all. Not only do they disclose the absence of an implied writer or reader; they call into question the very notion that the text represents or constitutes actions or events: its narrativity.
Keywords: first-person; third-person; narrative voices; Gérard Genette; Mauriac; voice; Thérèse Desquevroux; Le Noeud de vipères; implicit; I; he; implied writer; implied reader; reader; writer; narrativity